Microstructure, mechanical and electrical characterization of zirconia reinforced copper based surface composite by friction stir processing. (18th July 2018) - Kumar, Harikishor; Khan, M Z; Vashista, M
Abstract: Friction stir processing (FSP) has been established as a solid state technique for fabrication of metal matrix composites (MMCs). In the present investigation, FSP was used to disperse zirconia in copper to obtain copper matrix composite (CMC). For fabrication, a groove of known dimension was machined on to the surface of the copper plate (6 mm thick) and compactly filled with zirconia. After closing the groove with a pinless tool, it was processed with same tool material which had pin. The microstructural evaluation was carried by optical and scanning electron microscope (SEM). Observed micrograph confirmed uniform dispersion of zirconia in the copper matrix. The stir zone (SZ) of the fabricated composite displayed equiaxed and fine grain structure. Mechanical properties of the composite were assessed by microhardness and tensile test. The hardness of the fabricated composite in SZ improved significantly as compared to as received copper. Grain size reduction and uniform dispersion of zirconia contributed to the improvement in hardness. The tensile strength and electrical conductivity of the fabricated composite were found to be less as compared to as received copper. The post-assessment of the tensile specimen showed a reduction in ductility. The decreased electrical conductivity of the composite was ascribed to more scattering of electrons due to increased grain boundaries and non-conductive nature of zirconia.